Measurement of event-plane correlations in √sNN = 2.76 TeV lead-lead collisions with the ATLAS detector - Alconada Verzini, María Josefina (2014)
A measurement of event-plane correlations involving two or three event planes of different order is presented as a function of centrality for 7 μb-1 Pb+Pb collision data at sNN=2.76 TeV, recorded by the ATLAS experiment at the Large Hadron Collider. Fourteen correlators are measured using a standard event-plane method and a scalar-product method, and the latter method is found to give a systematically larger correlation signal. Several different trends in the centrality dependence of these correlators are observed. These trends are not reproduced by predictions based on the Glauber model, which includes only the correlations from the collision geometry in the initial state. Calculations that include the final-state collective dynamics are able to describe qualitatively, and in some cases also quantitatively, the centrality dependence of the measured correlators. These observations suggest that both the fluctuations in the initial geometry and the nonlinear mixing between different harmonics in the final state are important for creating these correlations in momentum space.